2014
DOI: 10.1186/s40478-014-0083-0
|View full text |Cite
|
Sign up to set email alerts
|

Soluble amyloid beta levels are elevated in the white matter of Alzheimer’s patients, independent of cortical plaque severity

Abstract: Alzheimer’s disease (AD) is the most common neurodegenerative disease and the leading cause of dementia. In addition to grey matter pathology, white matter changes are now recognized as an important pathological feature in the emergence of the disease. Despite growing recognition of the importance of white matter abnormalities in the pathogenesis of AD, the causes of white matter degeneration are still unknown. While multiple studies propose Wallerian-like degeneration as the source of white matter change, oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
45
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 71 publications
3
45
0
1
Order By: Relevance
“…In addition, Collins‐Praino et al . reported that WM Aβ peptides accumulate independently of the overall grey matter fibrillar amyloid pathology . These findings suggest that WM disease might be an early event in the pathogenesis of AD and may support our hypothesis in the current study.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, Collins‐Praino et al . reported that WM Aβ peptides accumulate independently of the overall grey matter fibrillar amyloid pathology . These findings suggest that WM disease might be an early event in the pathogenesis of AD and may support our hypothesis in the current study.…”
Section: Discussionsupporting
confidence: 90%
“…In the past few years, several studies have reported that soluble Aβ oligomers, rather than insoluble Aβ fibrils, are correlated with the extent of synaptic loss and the severity of cognitive impairment in AD . However, recognition of the importance of WM abnormalities in the pathogenesis of AD has been growing, and AD patients have been shown to exhibit increased WM levels of soluble Aβ, compared with non‐AD controls …”
Section: Discussionmentioning
confidence: 99%
“…The etiology of white matter lesions in AD is unknown and it has been proposed that oligodendrocyte degeneration occurs mainly secondary to the loss of neurons and axons (so called Wallerian degeneration) [49]. On the other hand, studies have shown that Aβ peptides are cytotoxic to oligodendrocytes and that they accumulate in white matter structures [12,16,32,65,80], raising the possibility that N-truncated Aβ4-x peptides produced by oligodendrocytes or in myelinated axons could be uniquely harmful. This putative pathogenic mechanism should be investigated further, which will likely require new animal models that account for a pro-amyloidogenic role of oligodendrocytes in the pathogenesis of AD.…”
Section: Discussionmentioning
confidence: 99%
“…A delay in amyloid plaque formation and complete absence of cognitive decline were observed when a Bri2-A␤42 fusion protein was used to express A␤42 in the mouse brain (40), suggesting that co-expression of Bri2 BRICHOS alleviates A␤42 neurotoxicity (19). The rh Bri2 BRICHOS concentrations detected in brains after intravenous injection (120 -880 nM) were higher than the soluble A␤40 and A␤42 concentrations reported in different regions of AD postmortem brain tissues (30 -120 pM) (41). A␤42 aggregation is extensively delayed (9), and most importantly, A␤42 toxicity to hippocampal slice preparations is reduced in the presence of substoichiometric concentrations of rh Bri2 BRICHOS (18); we speculate that the amounts of rh Bri2 BRICHOS that reach the brain after parenteral administration could effectively inhibit A␤ fibril formation and toxicity.…”
Section: Brain Penetrance Of Different Brichos Chaperone Domainsmentioning
confidence: 93%